Preparation and Characterization of Fe3O4 and Fe3O4/Bentonite Nanocomposite by Co-precipitation Method - Hashemian, Saeedeh; Saffari, Hossein (Asian Journal of Chemistry, 2011)
The particles of Fe3O4 and Fe3O4/bentonite were prepared by co-precipitation method. X-Ray diffraction patters indicated that the magnetic nanoparticles were pure Fe3O4 with a spinel structure and the binding of bentonite did not result in the phase change. The FTIR was used for characterization of these nano-ferrites. The TEM image of Fe3O4/bentonite was shown the particles diameters were 10 nm.